All Days 2010
DOI: 10.2118/128286-ms
|View full text |Cite
|
Sign up to set email alerts
|

Automation of Drawworks and Topdrive Management to Minimize Swab/Surge and Poor-Downhole-Condition Effects

Abstract: Unwary axial and rotational movement of the drill-string can cause formation fracturing or fluid influx resulting in costly remedial actions. With increasingly complex wellbore geometries and narrow geo-pressure windows, it is not always obvious for the Driller to estimate the real manoeuvring limits of the drawworks and the topdrive, especially under poor downhole conditions. The solution presented in this paper uses continuously updated safe guards applied to the drilling control system to maintain a downhol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 18 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…The drilling automation system continuously calculates maximum and minimum values for hook load, torque, and pump pressure, accounting for changing drilling conditions such as bit depth, temperatures, and cutting concentrations in the wellbore. In our case, the implemented approach for calculation of maximum and minimum values is model-based, using the observer-based approach described in [4]. The drilling control system is continuously updated with the maximum and minimum values for hook load, torque, and pump pressure.…”
Section: Overpull/set-down Weightmentioning
confidence: 99%
See 1 more Smart Citation
“…The drilling automation system continuously calculates maximum and minimum values for hook load, torque, and pump pressure, accounting for changing drilling conditions such as bit depth, temperatures, and cutting concentrations in the wellbore. In our case, the implemented approach for calculation of maximum and minimum values is model-based, using the observer-based approach described in [4]. The drilling control system is continuously updated with the maximum and minimum values for hook load, torque, and pump pressure.…”
Section: Overpull/set-down Weightmentioning
confidence: 99%
“…Some of the first ideas for applying automation to the drilling process date to 2004 [2]. It became clear that executing automated procedures could not be done without several protection mechanisms such as safe operating envelopes (SOE) and fault detection and mitigation (FDM) [3,4]. The application of standardized procedures under the protection of SOE and FDM functions have shown that automated drilling operations were both possible [5] and increased the efficiency [6].…”
Section: Introductionmentioning
confidence: 99%
“…While surface instrumentation has lagged in development, automation quality sensors are available (Florence and Iversen 2010;Ronaes et al 2012). Software models are being developed and tested that provide monitoring and prediction capability in real-time, as the well is drilled (Dashevskiy et al 2003;Rommetveit et al 2004;Iversen et al 2006;Cayeux and Daireaux 2009;Cayeux et al 2011;Wong et al 2013;among others). Software models address the entire automation spectrum.…”
Section: Current Statementioning
confidence: 99%
“…• Drill by wire: Such a system is an enhancement of the Drilling Control System to account for the side effects of the drill-string and drilling fluid movements on the drilling process [5] [6]. It implements safe guards to maneuver the drilling machineries in a way which reduces the risk for causing drilling incidents like formation fluid influx, hole collapse, formation fracturing, cuttings accumulation.…”
Section: Concurrent Drilling Automationsmentioning
confidence: 99%